The association of modifiable and socio‐demographic factors with first transitions from smoking to exclusive e‐cigarette use, dual use or no nicotine use: Findings from the Avon Longitudinal Study of Parents and Children United Kingdom birth cohort - Andrayas, Alexandria; Heron, Jon; Khouja, Jasmine; Jones, Hannah; Munafò, Marcus; Sallis, Hannah; Hines, Lindsey; Curnow, Elinor (Addiction, 2025)
Background and Aims: E‐cigarettes can aid smoking cessation and reduce carcinogen exposure. Understanding differences in characteristics between young adults who quit smoking, with or without e‐cigarettes, or dual use can help tailor interventions. The aim of this study was to describe first transitions from smoking and explore substance use, sociodemographic, and health characteristic associations with the probability of each possible first transition from smoking. Design and Setting: Longitudinal birth cohort data from the Avon Longitudinal Study of Parents and Children (ALSPAC), conducted in the United Kingdom. Participants: A total of 858 participants were included who reported tobacco smoking in the past month at age 21 during a questionnaire collected in 2013. Measurements: The first reported non‐exclusive smoking event following smoking, observed approximately annually between ages 22 and 30, was categorized as either no nicotine use, exclusive e‐cigarette use, or dual use. Discrete‐time subdistribution hazard models were used to examine associations between different covariates, including substance use, sociodemographic, and health characteristics, with the probability of each first transition from smoking. Analyses were adjusted for early‐life confounders and weighted to mitigate bias. Findings Among participants, 52% stopped nicotine use, 27% reported dual use, and 9% used e‐cigarettes exclusively. Smoking weekly or more (Subdistribution Hazard Ratio [SHR] = 0.28, 95% Confidence Interval [CI] = 0.22–0.35), having many friends who smoke (SHR = 0.64, 95% CI = 0.50–0.81), and lower education (SHR = 0.68, 95% CI = 0.52–0.90) reduced the likelihood of no nicotine use and increased dual use (frequent smoking SHR = 3.00, 95% CI = 1.96–4.59; peer smoking SHR = 1.55, 95% CI = 1.07–2.24; education SHR = 1.72, 95% CI = 1.03–2.90). Cannabis use (SHR = 0.67, 95% CI = 0.49–0.92), drug use (SHR = 0.77, 95% CI = 0.59–0.99), less exercise (SHR = 0.71, 95% CI = 0.53–0.95), and early parenthood (SHR = 0.46, 95% CI = 0.27–0.79) reduced no nicotine use. Higher BMI (SHR = 1.58, 95% CI = 1.08–2.31) increased dual use. Conclusions: In the United Kingdom, young adults who smoke frequently, have more smoking peers, have lower education, engage in drug use, exercise less, or become parents early appear to be less likely to stop nicotine use than other young adults who smoke. Frequent smoking, peer smoking, lower education, and higher body mass index also appear to be associated with increased dual use of cigarettes and e‐cigarettes.